2015
DOI: 10.7554/elife.06414
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic sodium spikes are required for long-term potentiation at distal synapses on hippocampal pyramidal neurons

Abstract: Dendritic integration of synaptic inputs mediates rapid neural computation as well as longer-lasting plasticity. Several channel types can mediate dendritically initiated spikes (dSpikes), which may impact information processing and storage across multiple timescales; however, the roles of different channels in the rapid vs long-term effects of dSpikes are unknown. We show here that dSpikes mediated by Nav channels (blocked by a low concentration of TTX) are required for long-term potentiation (LTP) in the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
109
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(127 citation statements)
references
References 132 publications
12
109
2
Order By: Relevance
“…Although these studies did not rigorously establish the unique role of NMDA spikes as in our experiments, they are consistent with our conclusion that dSpikes rather than bAPs provide the critical depolarization for LTP. Thus, NMDA spikes appear to be important for LTP at synapses in diverse brain regions, but other synapses have been shown to depend on other types of supralinear signalling8121314. It should be noted that in our preparation a single bAP almost never triggered an NMDA spike and did not induce LTP.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Although these studies did not rigorously establish the unique role of NMDA spikes as in our experiments, they are consistent with our conclusion that dSpikes rather than bAPs provide the critical depolarization for LTP. Thus, NMDA spikes appear to be important for LTP at synapses in diverse brain regions, but other synapses have been shown to depend on other types of supralinear signalling8121314. It should be noted that in our preparation a single bAP almost never triggered an NMDA spike and did not induce LTP.…”
Section: Discussionmentioning
confidence: 60%
“…Previous work in diverse brain areas has shown that dendritic spikes generate the supralinear signal triggering plasticity at synapses where LTP can occur independently of bAPs56111213. Specifically for NMDAR-dependent dendritic spikes, in vivo investigations have provided correlative evidence for their role in synaptic plasticity in CA1 pyramidal cells41, in motor cortex10 and in barrel cortex11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of action potential firing and the subsequent neurotransmitter release, small, albeit significant calcium changes are seen in the dendrite and more specifically, the spines of neurons. There, the more subtle role of calcium in controlling encoding and dendritic excitability through local calcium transients is now becoming clear, and includes measures in behaving animals [90; 91; 92; 93; 94; 95; 96]. In field CA1, primary hippocampal neurons are able to integrate signals coming from distal inputs from the entorhinal cortex, and more proximal inputs emitting from area CA3.…”
Section: Cellular Calcium Transients Have a Dendritic Originmentioning
confidence: 99%
“…For instance, with the theta burst protocol for inducing LTP (Fig. 5A), proximal synaptic LTP requires pairing with backpropagating action potentials, but distal synapses recruit dendritic spikes and do not require backpropagating action potentials (Golding et al, 2002;Kim et al, 2015;Magee and Johnston, 1997).…”
Section: Degeneracy In Calcium Regulation and In The Induction Of Synmentioning
confidence: 99%